PENINGKATAN HASIL BELAJAR PKn TEMA BUDI PEKERTI MELALUI PENERAPAN METODE PEMBELAJARAN TALKING STICK SISWA KELAS I SDN 3 TAMBAK KABUPATEN GRESIK - Sanawiyah (CENDEKIA: Jurnal Studi Keislaman, 2016)
The purpose of this study was to determine the effectiveness of teaching methods talking stick in improving learning outcomes of PKn (Civics) Theme Character at grade 1 SDN 3 Tambak Tambak Subdistrict of Gresik District in the academic year 2014-2015. This research is expected to be useful for readers and teachers in improving the quality of learning in the classroom, especially through the method of Talking Stick. The subject of research in this PTK is the first grade students SDN 3 Tambak Tambak Subdistrict Gresik in second semester in the academic year 2014-2015. The number of students is 30 children. The time of the research is on March 9 until 16, 2015. Based on the analysis result, it got a description that the application of the talking stick learning methods could improved learning outcomes of PKn (Civics) Theme Character at grade 1 SDN 3 Tambak Tambak District of Gresik in the academic year 2014-2015 with the completeness rate reaching 79.1%.